Keragaan dan Produktivitas Perkebunan Lada Tumpangsari Kopi di Lampung Utara - Prasmatiwi, Fembriarti Erry; Evizal, Rusdi (JURNAL AGROTROPIKA, 2020)
North Lampung Regency is the main producer of Lampung black pepper, which is generally in the form of a poly-culture system of pepper cultivation. This study aims to study the performance and productivity of the pepper plant which is intercropped with coffee by farmers in North Lampung. This study used a survey method and conducted in North Lampung by taking 2 samples of the sub-districts purposively, namely Abung Barat and Abung Tengah. From each district, 2 villages were selected purposively. Primary data were collected by interviewing 93 sample farmers who were randomly sampled. To deepen the performance of planting, visits and observations of farmers' fields were conducted. The results of this study concluded that: (1) 96% of farmers applied a poly-culture pepper plantation system. Intercropping pepper plantations have a lower pepper plant population but the presence of intercropping can cause land use efficiency to increase by up to 30%;(2) The poly-culture pepper fields are managed less intensively as indicated by the low fertilizer dosage and the high mortality rate of pepper, which reaches 7-10% of plants per year; (3) The productivity of this intercropping system is pepper yield (conversion of SPH 1600 trees / ha) reaching 230-260 kg / ha or based on factual population reaching 155-267 kg/ha, coffee yield 166-221 kg/ha, and yield of Pithecellobium jiringa 24 -28 kg/tree; (4) According to farmers' perceptions, the main constraints faced by farmers (80.2% of farmers) were the attack of pepper foot rot disease, low prices for pepper, and high mortality of pepper trees. However, most farmers (88.9% of farmers) said they would not replace pepper with other crops. Keywords: Black pepper, coffee, Pithecellobium jiringa, poly-culture, yield